When the body displaces the mind : stress, trauma, and somatic disease - Stora, Jean Benjamin, 1934- (Karnac, 2007)
Can the mind really generate a physical disease? Conversely, can the body cause mental illness? What do we know today about their interaction? The relations between body and mind are the source of many problems that are currently treated separately by psychoanalysts and doctors because of the compartmentalisation between their disciplines. Despite differences in clinical practice, we all stand to benefit from a common understanding of the reciprocal influences of the mind and the body and the ways in which these are interrelated. It is time to stop treating the body in isolation from treatment.